2020
DOI: 10.3390/ph13010006
|View full text |Cite
|
Sign up to set email alerts
|

2019: An Awesome Year for Pharmaceuticals

Abstract: Ending the year is an opportunity to reflect on the past, in particular the past twelve months [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…I knew exciting weeks with an overcrowded office table. Years have passed, and Pharmaceuticals is now a successful Journal [3,4]. It is time for me to face a new adventure, and I found that opportunity in the launch of Drugs and Drug Candidates (ISSN: 2813-2998) [5].…”
Section: From Pharmaceuticals To Drugs and Drug Candidatesmentioning
confidence: 99%
“…I knew exciting weeks with an overcrowded office table. Years have passed, and Pharmaceuticals is now a successful Journal [3,4]. It is time for me to face a new adventure, and I found that opportunity in the launch of Drugs and Drug Candidates (ISSN: 2813-2998) [5].…”
Section: From Pharmaceuticals To Drugs and Drug Candidatesmentioning
confidence: 99%